Penyeimbangan Lintasan Produksi Ribbed Smoke Sheet Untuk Meningkatkan Efisiensi Lintasan Menggunakan Metode Theory Constraint - Novri Yohannes Harianja; Irwan Soejanto; Eko Nursubiyantoro (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
PT. Perkebunan Nusantara IX is a State-Owned Enterprise (BUMN) manufacturing rubber processing to produce Ribbed Smoke Sheets (RSS) located in Salatiga City, Central Java. Several things are not done by the company, namely the inefficient trajectory caused by the company's target being too high compared to the output produced. The production process has an imbalance in the trajectory, in which there is still an accumulation of materials/goods in process in several workstations so that actual production is not meet production targets, and the company is having difficulty meeting market demand. So it is necessary to balance the trajectory to answer these problems. Increasing the efficiency of the production balance can be obtained by balancing the trajectory using the theory constraint method aimed at reducing idle time and accumulation of goods so that the production process becomes more efficient. The method that can be used is CPM/PERT. The steps used are grouping work elements into workstations, calculating the value of workload, tracking efficiency, smoothing index, and balance delay, which are then compared based on the two methods. The results obtained are that the RSS production line has a high track efficiency value based on comparing the CPM/PERT method. Hence, the suggestion for the Ribbed Smoke Sheet (RSS) production line so that the line efficiency value is high following the CPM/PERT method is to make three workstations so that the value obtained is the track efficiency is 85% and increases by 21% from the initial track efficiency value, from 64% to 85%. The idle time value decreased from the initial 4.66 minutes to 1.51 minutes, the Balance Delay value also decreased from 37% to 16%, and the Smoothing Index value decreased from the initial 3.3 minutes to 1.08 minutes.